The effect of auditor attributes on perceived audit quality: evidence from Jordan
The poor of audit quality has become one of the phenomenal challenges facing the financial sector in Jordan and how to offer directives and policies to generate high-quality of auditing. This study is motivated by the problem of tax evasions in Jordan focusing on the perspective of audit quality among Jordanian auditors as one of the possible solution. Thus, the purpose of this study is to examine the attributes affecting audit quality for Jordanian auditors. This study is based on four variables that are used to understand and analyze the level of audit quality for Jordanian auditors. The four variables that are measured in current study are: audit tenure, audit firm size, the level of compliance toward ethical rules and the reliance on internal audit work. The data were collected through the distribution of questionnaires to 200 respondents in Jordanian auditors and processed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) software for the purpose of this study. By using descriptive analysis and structural equation model, the findings of the study show that there is a positively and significant effects between audit tenure, audit firm size, the level of compliance toward ethical rules and audit quality. On the other hand, the reliance on internal audit work indicates a negative and insignificant effect with audit quality. In addition, this study conducted further analysis by control the respondents based on Big 4 audit firms and non-big 4 audit firms. Based on the results, the reliance on internal audit work indicate a positive and significant results for auditor from Big 4 audit firm but negative and significant results for auditors from non-big 4 audit firm. Furthermore, based on the demographic profile majority of the respondent is from non-big 4 audit firm which could provide a unique result. The findings suggest that the non-big 4 audit firm must improve the communication between the internal and external auditors to enhance audit quality in Jordan.